The Influence of Project Citizen and Creative Thinking Ability on the Civic Skills of Class VII Students of SMP Negeri 3 Tigapanah - Melly Andriani Br Ginting; James Ndona; Dede Ruslan (UNIVERSITAS PAKUAN, 2023)
Research was carried out regarding the factual low civic skills of class VII students due to the inappropriate choice of learning model. Thus, the right learning model is expected to be able to provide understanding and interest in students so that the ability to think creatively emerges. This research was carried out with the aim of finding out: 1) the results of civic skills taught using the project citizen model and teams games tournament, 2) the results of the civic skills of groups of students who have high and low creative thinking abilities, 3) the interaction between the project citizen model and thinking abilities creative towards students' civic skills. This research was carried out at SMP Negeri 3 Tigapanah with samples in class VII. The method used in this research is an experimental research method. This research design uses a 2x2 factorial design. There are two classes in this research, namely the experimental class with class VII-1 students and the control class with class VII-2 students. The results of the research show that 1. There is an influence of Project Citizen in influencing civic skill results, namely that Project Citizen has more impact than teams games tournaments, 2. There is an influence of creative thinking ability in influencing civic skill results, namely high creative thinking ability has more impact than ability. low creative thinking, and 3. There is an interaction between project citizenship and creative thinking ability in influencing civic skills results with F count 7.06 . The results of this research conclude that choosing the right learning model can provide positive results and creative thinking abilities to students.